Pembelajaran Kontekstual sebagai Strategi Pengembangan Literasi Manusia - Faizah, Ima; Handayani, Puspita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to analyze how contextual learning is implemented in the Kemuhammadiyahan course and how it affects human literacy abilities. The method used is quantitative and descriptive qualitative, that carried out by exploring student responses as research objects by filling out questionnaires by all students who take part in the study, totaling 228 students. Data is analyzed by validity test, reliability test, and effectiveness test. The results showed that the contextual learning strategies by real work lecture methods or project-based learning can help students learn to communicate with various types of people and community groups, learn to cooperate with friends and the community, learn to interact and adapt to various cultures, moral and ethical values in society, as well as think creatively and solutely, to improve students' human literacy skills.